Brachialis strain in a collegiate wrestler: a case report - Geiselman, J.; Gillespie, R.; Miller, A. (International Journal of Athletic Therapy & Training, 2020)
A 22-year-old male varsity collegiate wrestler presented for general chiropractic care for an unrelated condition and noted right elbow pain that had progressively increased over the past few weeks. The athlete was diagnosed with a right brachialis strain and advised to follow up with his athletic trainer for co-management of his injury. The patient responded positively to prescribed treatments and rehabilitation to decrease pain and restore functionality (<14 days) while only missing one competitive match. The location of the brachialis muscle and scarcity of literature makes diagnosis and treatment complex. The physical examination and conservative treatment presented in this report demonstrate the need for comprehensive and exploratory examination and co-management of wrestling athletes with a brachialis strain.